Thyroglobulin Levels in Patients who have Undergone Hemithyroidectomy for Differentiated Thyroid Cancer. An Assessment of Levels and Trends at a Tertiary Referral Centre - Munnagi, Ashwini; Pillai, Vijay; Bushan, R. Vidhya; Shetty, Vivek; Subramaniam, Narayana; Shivaprasad, K. S.; Khadilkar, Kranti; Sooragonda, Basavaraj G.; Lakhsmikantha, Akhila; Rekha, Pobbisetty Radhakrishnagupta; Zaidi, Shaesta Naseem; Batra, Nishtha; Kannan, Subramanian (South Asian Journal of Cancer, 2021)
Serum thyroglobulin (Tg) and thyroglobulin antibody (TgAb) levels are used to monitor patients with differentiated thyroid cancer (DTC) after total thyroidectomy with or without radioiodine (RAI) ablation. However, they are also measured in patients who are treated with thyroid lobectomy (TL)/hemithyroidectomy (HT). Data on the levels of Tg and its trend in those undergoing TL/HT is sparse in India. We reviewed retrospective data of DTC patients who underwent TL/HT and were followed-up with postoperative Tg levels between 2015 and 2020. Out of 247 patients, 17 had undergone either TL or HT, which included papillary thyroid cancer (n = 12), follicular thyroid cancer (n = 4), and noninvasive follicular thyroid neoplasm with papillary-like nuclear features (NIFTP) in 1 patient. All patients with DTC had tumor size < 4 cm (T1/2, clinical N0, Mx). The median follow-up was 15 months (range, 1–125) and the median Tg level was 7.5 ng/mL (interquartile range [IQR]; 3.6, 7.5) and ranged from 0.9 to 36.7 ng/mL. The median thyroid-stimulating hormone (TSH) level was 2.03 IU/L (IQR; 1.21, 3.59) and it ranged from 0.05 to 8.54 IU/L. As of last follow-up, none of them underwent completion thyroidectomy; however, eight patients had a decline in Tg ranging from 8 to 64%, four patients had increase in Tg ranging from 14 to 145%, three patients had stable Tg, and one of them had an increase in TgAb titers. As per American Thyroid Association (ATA) response-to-treatment category, six patients had indeterminate response, five patients had biochemical incomplete response, four patients had excellent response, and two did not have follow-up Tg and TgAb levels. While absolute values of Tg were well below 30 ng/mL in almost all patients with HT/TL, the Tg trends were difficult to predict, and only 23% of patients were able to satisfy the criteria for “excellent response” on follow-up. We suggest keeping this factor in mind in follow-up and while counselling for HT in patients with low-risk DTC.
Keywords: serum thyroglobulin; hemithyroidectomy; lobectomy; Tg levels; differentiated thyroid cancer